The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1479-5876-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects human renal proximal tubular cells from hypoxia/reoxygenation injury via inhibiting endoplasmic reticulum and mitochondrial stress pathways

Abstract: BackgroundIschemia/reperfusion injury plays a crucial role in renal transplantation, and represents a significant risk factor for acute renal failure and delayed graft function. The pathophysiological contribution of endoplasmic reticulum and mitochondria stress to ischemia/reperfusion injury has also been highlighted. Berberine (BBR) has been showed to attenuate ischemia/reperfusion injury by inhibiting oxidative stress. The study was carried out to investigate whether the pretreatment of BBR could reduce hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 37 publications
1
71
0
1
Order By: Relevance
“…25 In parallel, two ER stress hallmarks, GRP78 and CHOP, showed increased protein levels after hypoxia and ER stress, and participated in hypoxia/reoxygenation induced apoptosis in human renal proximal tubular epithelial cell line (HK-2 cells). 49 However, those parameters were significantly suppressed by berberine pretreatment. 49 It was also demonstrated that tauroursodeoxycholic acid (TUDCA) pretreatment had a nephroprotective effect on ischemia-induced AKI by inhibiting ER stress and by blocking GRP78 and CHOP expression, reducing Caspase 12 activation, and inhibiting cell apoptosis.…”
Section: Apoptosis Promoting Effect Of Er Stress and Interventionsmentioning
confidence: 83%
See 1 more Smart Citation
“…25 In parallel, two ER stress hallmarks, GRP78 and CHOP, showed increased protein levels after hypoxia and ER stress, and participated in hypoxia/reoxygenation induced apoptosis in human renal proximal tubular epithelial cell line (HK-2 cells). 49 However, those parameters were significantly suppressed by berberine pretreatment. 49 It was also demonstrated that tauroursodeoxycholic acid (TUDCA) pretreatment had a nephroprotective effect on ischemia-induced AKI by inhibiting ER stress and by blocking GRP78 and CHOP expression, reducing Caspase 12 activation, and inhibiting cell apoptosis.…”
Section: Apoptosis Promoting Effect Of Er Stress and Interventionsmentioning
confidence: 83%
“…49 However, those parameters were significantly suppressed by berberine pretreatment. 49 It was also demonstrated that tauroursodeoxycholic acid (TUDCA) pretreatment had a nephroprotective effect on ischemia-induced AKI by inhibiting ER stress and by blocking GRP78 and CHOP expression, reducing Caspase 12 activation, and inhibiting cell apoptosis. 48 There are other interventions being explored.…”
Section: Apoptosis Promoting Effect Of Er Stress and Interventionsmentioning
confidence: 83%
“…In addition, the anti-apoptotic potential of berberine against renal injury is in agreement with the previous findings. 81 …”
Section: Discussionmentioning
confidence: 99%
“…[159] . Berberine has been reported to ameliorate proinflammatory cytokine-induced ERS in human intestinal epithelial cells [160] , reduce hypoxia/reoxygenation-induced human renal proximal tubular cell injury [161] , and inhibit the human immunodeficiency virus protease inhibitor-induced inflammatory response in murine macrophages [162] . Berberine has also been suggested to have an anti-hypertensive property [163] .…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%